The Transformation of Quranic Studies in the Era of Artificial Intelligence: An Epistemological Shift from Classical Scientific Tradition to the Digital Ecosystem - Muhammad Safrizal; Stephen Baker; Josef Peterson; Zara Amaefule; Khalid S Hamad (Yayasan Albahriah Jamiah Indonesia, 2026)
The development of artificial intelligence as a digital knowledge infrastructure has fundamentally changed the landscape of contemporary Quranic studies. Unlike previous approaches that tended to position technology as an assistive instrument, the integration of AI in the form of semantic search engines, natural language processing, and interpretation recommendation systems presents epistemological issues that have not been systematically studied, particularly regarding the shift in knowledge sources, truth validation mechanisms, and the configuration of interpretive subjects within the Quranic scholarly tradition. This study aims to critically analyze the epistemological transformation of Quranic studies from a classical scientific framework to an AI-based digital ecosystem, focusing on the reconstruction of knowledge authority, changes in interpretive methodology, and the restructuring of subject-knowledge relations. This study uses a qualitative method with an epistemological-critical approach, analyzing the latest academic literature in the field of Quranic studies and technology, as well as a conceptual review of concrete practices of AI utilization in digital Quranic studies. The results show that the integration of AI triggers a multidimensional epistemological shift, namely: first, the reconstruction of knowledge sources from the authority of scholars and texts to an aggregative algorithmic database; Second, the transformation of interpretive methodology from in-depth, discipline-based reading to rapid, computationally-assisted analysis; Third, the shift in truth validation mechanisms from scientific consensus to technological and statistical verification; Fourth, the emergence of new epistemic subjects that do not fully fall within the framework of conventional scholars or academics. These findings emphasize that AI is epistemologically non-neutral and forms a new logic of knowledge production that demands theoretical reformulation in the epistemology of contemporary Quranic studies.